Determinants of Elderly Migration to Old Age Homes in Nepal: Impact of Modernization, Family Dynamics, and Societal Shifts in Urban Nepal - Gautam, Tara Prasad; Mishra, Anjay Kumar (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 3 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
Background: In Nepal, elderly individuals have traditionally occupied a respected position within family structures, with care provided by family members in a joint family system. However, recent societal shifts towards nuclear families and individualism have resulted in many elders lacking traditional family support, leading to increased migration to old age homes (OAHs), particularly in urban areas like the Kathmandu Valley. Objective: This study examines the socio-economic, cultural, and health-related factors that compel 274 elderly individuals to leave their original homes for OAHs. It aims to explore how modernization, changing family dynamics, and evolving societal values influence these decisions, contributing to an eldercare model that diverges from Nepal’s cultural heritage. Methods: Through survey analysis, the research assesses the emotional well-being of OAH residents, their quality of life, and their perspectives on family and community connections. It further investigates the perceived repercussions on family relationships and community structures while evaluating state policies related to elder welfare. Findings: The findings indicate that financial insecurity, limited caregiving capacity within nuclear families, and societal neglect are prominent factors influencing this transition. Many elderly individuals experience emotional challenges and a sense of isolation in OAHs, despite some reporting satisfactory quality of life indicators. Conclusion: This research provides insight into the changing eldercare landscape in Nepal and highlights the urgent need for supportive policies to address the evolving needs of an aging population in the context of modernization. The study emphasizes the importance of fostering family connections and community support for elderly individuals transitioning to OAHs.